2018
DOI: 10.1007/s00408-018-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Chronic Bronchitis with Preserved Ratio and Impaired Spirometry (PRISm)

Abstract: In terms of airway wall area and emphysema index, patients with chronic bronchitis with PRISm were essentially no different than those with chronic bronchitis without abnormal spirometry, whereas for symptoms, they are more like GOLD 1 and 2 patients. Our findings show that it is not yet clear whether it constitutes an intermediate stage of chronic bronchitis with normal lung function that progression to early COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…(34,35) Many of these excluded individuals have PRISm, and although they do not meet the diagnostic spirometric criteria for COPD they exhibit similar changes such as small airways disease, emphysema and gas trapping. (4,36,37) Little focus has been given to whether asthma contributes to PRISm, despite high rates of selfreported asthma in other PRISm cohorts (21% in COPDgene (2) ) and in this UKBB cohort reported asthma among PRISm was 18.4%. (4) There are many plausible ways asthma could contribute to both PRISm and airflow obstruction.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(34,35) Many of these excluded individuals have PRISm, and although they do not meet the diagnostic spirometric criteria for COPD they exhibit similar changes such as small airways disease, emphysema and gas trapping. (4,36,37) Little focus has been given to whether asthma contributes to PRISm, despite high rates of selfreported asthma in other PRISm cohorts (21% in COPDgene (2) ) and in this UKBB cohort reported asthma among PRISm was 18.4%. (4) There are many plausible ways asthma could contribute to both PRISm and airflow obstruction.…”
Section: Discussionmentioning
confidence: 86%
“…(34, 35) Many of these excluded individuals have PRISm, and although they do not meet the diagnostic spirometric criteria for COPD they exhibit similar changes such as small airways disease, emphysema and gas trapping. (4, 36, 37)…”
Section: Discussionmentioning
confidence: 99%
“…e PRISm group showed decreased lung capacity and higher mean lung density [25]. Kirby et al found small airway pathological changes in early/ mild COPD patients using CT total airway count, but their lung function parameters (such as FEV1 and FVC) are still in the normal range, suggesting that small airway impairment is appeared before lung function damage [26].…”
Section: Discussionmentioning
confidence: 98%
“…Risk factors include age, female sex, a history of smoking, diabetes mellitus, and obesity 5,7,15,16 . Moreover, increased dyspnoea, reduced 6-min walk distance 1 , and reduced health-related quality of life 17,18 have been reported in individuals with PRISm.The Genetic Epidemiology of COPD (COPDGene) study and other reports discussing PRISm 1-3,8,18 have explained the condition using medical data 4,6,9 . However, few studies have focused on community-dwelling individuals 7 .…”
mentioning
confidence: 99%
“…The Genetic Epidemiology of COPD (COPDGene) study and other reports discussing PRISm 1-3,8,18 have explained the condition using medical data 4,6,9 . However, few studies have focused on community-dwelling individuals 7 .…”
mentioning
confidence: 99%